TEMPERATURE AND ACETIC ACID CONCENTRATION OPTIMATION IN THE EPOXIDATION REACTION OF PALM OIL METHYL ESTER - Emma Savitri, dan Christopher Aditya Sivananda, Edy Purwanto, (Jurnal Teknik Kimia, 2011)
Vegetable oils are rich in content unsaturated fatty acid from the type of oleic acid, linoleic acid andlinolenic acid that can be converted to epoxide groups. Epoxidized oil has many useful applications such asplastisizer to improve flexibility, elasticity and stability under the influence of heat and radiation. In thisresearch, palm oil was converted first to become palm oil methyl ester (POME), followed by epoxidationreaction to produce epoxidized palm oil methyl ester (EPOME). Response surface method (RSM) was performedfor optimization and to study the influence of reaction temperature and molar ratioPOME/CH3COOH on the conversion reaction and oxirane value. An optimal reactional condition was shownby high oxirane content which was in the form of oxirane counts/number. Epoxidation reaction was run inthe batch reactor using acetic acid as an oxygen carrier. Central Composite Design (CCD) with two independentvariables and two response function was utilized to investigate the effect of input variables. Theresult shows that reaction conversion increased with the rise of reaction temperature and molar ratio ofPOME/CH3COOH before reaching the maximum point, and then it monotonously decreased. The optimaloperating condition for epoxidation reaction was indicated by maximum oxirane value which could bereached by the reaction temperature of 56.3 oC and molar ratio POME/CH3COOH of 1:0.43Key words: epoxidation, methyl ester, oxirane, palm oil